2021
DOI: 10.1007/s00167-021-06529-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related cancellation of elective orthopaedic surgery caused increased pain and psychosocial distress levels

Abstract: Purpose Health care systems in most European countries were temporarily restructured to provide as much capacity as possible for the treatment of coronavirus disease 2019 (COVID-19) patients. Subsequently, all elective surgeries had to be cancelled and postponed for months. The aim of the present study was to assess the pretreatment health status before and after COVID-19-related cancellation and the psychosocial distress caused by the cancellation. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 37 publications
5
28
0
2
Order By: Relevance
“…Increased pain was also found by Knebel et al [ 11 ], but higher use of pain medication was not found. The dimension of anxiety/depression in the EQ-5D-5L was not significant, which strengthens the results from Endstrasser et al [ 6 ] who found no influence on mental health and was partly in line with Knebel et al [ 11 ] who found psychosocial distress only for middle-aged women. Given that the minimum clinically important difference (MCID) for the WOMAC Score ranging between 2 and 10 points (Siviero et al [ 24 ], Clement et al [ 3 ]), the 4.7 points found in this study is right in between, thus casting doubt on clinical relevance.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Increased pain was also found by Knebel et al [ 11 ], but higher use of pain medication was not found. The dimension of anxiety/depression in the EQ-5D-5L was not significant, which strengthens the results from Endstrasser et al [ 6 ] who found no influence on mental health and was partly in line with Knebel et al [ 11 ] who found psychosocial distress only for middle-aged women. Given that the minimum clinically important difference (MCID) for the WOMAC Score ranging between 2 and 10 points (Siviero et al [ 24 ], Clement et al [ 3 ]), the 4.7 points found in this study is right in between, thus casting doubt on clinical relevance.…”
Section: Discussionsupporting
confidence: 59%
“…The limited literature about COVID-19 and preoperative health, measured using patient-reported outcome measurements (PROM), indicated increasing pain for postponed patients, decreasing physical function and activity, and ambiguous results for mental health [ 6 , 11 ]. However, a small sample size study indicated increasing health-related quality of life (HRQoL) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Das Vertrauen in das deutsche Gesundheitssystem, in die behandelnde Klinik und in die behandelnden Ärztinnen und Ärzte war in der vorliegenden Stichprobe hoch. Dies zeigte sich auch in anderen Patientengruppen 30 .…”
Section: Diskussionunclassified
“…Erste Studien aus der Orthopädie in Deutschland zeigen, dass eine Verschiebung von Operationen zusätzliche Schmerzen und Analgetikaeinnahme verursachten [20]. Für Tumorerkrankungen und deren Behandlung liegen mittlerweile Daten vor, dass die Verschiebung der indizierten Therapie erheblichen negativen Einfluss auf die Prognose und das Langzeitüberleben zeigt [21].…”
Section: Diskussionunclassified